A Universally Applicable Strategy for Construction of Anti‐Biofouling Adsorbents for Enhanced Uranium Recovery from Seawater. Issue 13 (20th March 2019) - Yu, Qiuhan; Yuan, Yihui; Wen, Jun; Zhao, Xuemei; Zhao, Shilei; Wang, Dong; Li, Chaoyang; Wang, Xiaolin; Wang, Ning
Abstract: The ocean reserves 4.5 billion tons of uranium and amounts to a nearly inexhaustible uranium supply. Biofouling in the ocean is one of the most severe factors that hazard uranium extraction and even cause the failure of uranium extraction. Therefore, development of uranium adsorbents with biofouling resistance is highly urgent. Herein, a strategy for constructing anti‐biofouling adsorbents with enhanced uranium recovery capacity in natural seawater is developed. This strategy can be widely applied to modify currently available carboxyl‐contained adsorbents, including the most popular amidoxime‐based adsorbent and carboxyl metal organic framework adsorbent, using a simple one‐step covalent cross‐link reaction between the antibacterial compound and the adsorbent. The prepared anti‐biofouling adsorbents display broad antibacterial spectrum and show more than 80% inhibition to the growth of marine bacteria. Benefitting from the tight covalent cross‐link, the anti‐biofouling adsorbents show high reusability. The modified amidoxime‐based adsorbents show enhanced uranium recovery capacity both in sterilized and bacteria‐contained simulated seawater. The anti‐biofouling adsorbent Anti‐UiO‐66 constructed in this study exhibits 24.4% increased uranium recovery capacity, with a uranium recovery capacity of 4.62 mg‐U per g‐Ads, after a 30‐day field test in real seawater, suggesting the strategy is a promising approach for constructing adsorbents with enhanced uranium extraction performance. Abstract : A universally applicable strategy for constructing anti‐biofouling adsorbents is developed to fabricated adsorbents with enhanced uranium recovery capacity from seawater. The strategy is based on a one‐step simple chemical reaction and can be used to modify all carboxyl group‐contained adsorbents, including the most popular amidoxime‐based uranium adsorbents, and can endow the adsorbents with resistance to biofouling.